Development and validation of an instrument to measure adult educators' power and influence tactics in program planning practice. - Baiyin Yang (Adult Education Research Conference, 1997)
This paper reports a study designed to develop and validate an instrument to measure adult educators' power and influence tactics in program planning practice. The results indicate that planning behaviors are measurable and accountable by the planning theory that takes into account organizational political contexts.